Sistem Informasi Geografis Tempat Wisata Berbasis Web Berbasis Blog di Kota Tomohon - Telly Hetty Isje Kondoj; Jeannlly Adri Solang; Frans Victor Rattu (Politeknik Pariwisata Makassar, 2023)
Producing a Web-based Information System blog with data visualization containing information on the location of tourist objects that are presented to the public as a promotion of Tomohon tourism based on a Web Blog According to Gween Solomon, lynne Lynne, Web 2.0 Guide for educators (Jakarta: Ptindex index) Blog stands for weblog. a weblog is a type of website developed and managed by individuals using online software or a very user-friendly hosted platform, with room to write. Blogs feature instant online publications and invite the public to read and provide feedback as comments with the existence of a web blog created on blogger.com containing 10 tomohon attractions, it is hoped that it l make it easier for people to determine trips witwithatravele tomohon area which has more than 90 natural, cultural and artificial attractions. The blog content created includes 10 superior tourist attractions that are still operating well and relatively close to the city center of Tomohon and a Google Maps link to allow readers to find location points to be able to reach the most important attractions. This blog can be accessed with electronic devices such as (mobile phones and laptops) that have an internet network.